ANALISIS KAPASITAS PERSIMPANGAN TAK BERSINYAL PADA PERSIMPANGAN JL.RAJAWALI -JL. ANTANG ( Capacity Analysis Of Unsignaled Intersections At Interssions Jl. Rajawali -Jl. Antang ) - Yanshon Happy; Rachmadi Maulana.B.L (Fakultas Teknik Universitas Kristen Palangka Raya, 2022)
We often encounter traffic problems in big cities and small towns. For example, in the Capital City of Central Kalimantan Province, namely the City of Palangka Raya, the problem of traffic jams and chaos often occurs at road junctions, especially at unsignalized junctions, the JL.Rajawali - JL Antang intersection. This is influenced by several factors, namely the increasing volume of traffic and the number of motorists not obeying traffic rules. Analyzing the capacity and performance level of an unsignalized intersection, data is collected from the field, in the form of intersection geometry data, the type and number of vehicles crossing the intersection after being multiplied by the equivalent number of each vehicle, so that uniformity is obtained in the unit of passenger cars (SMP). . Then the capacity and performance level of the intersections were calculated which included the degree of saturation, and the delay of the intersections using the Indonesian Highway Capacity Manual (MKJI 1997). The results of the analysis obtained, the capacity value (C) of the intersection is 3827.16 pcu/hour, while from the three observation days, the largest value for traffic volume is 2633.20 pcu/hour on Monday at 06.30-07.30 WIB, the degree of saturation (DS) of 0.68 on Monday at 06.30-07.30 WIB, and the deviation delay of 13.45 sec/smp on Monday at 06.30-07.30 WIB. Then the capacity is obtained at the intersection of JL..Rajawali. – JL. Antang. Palangka Raya City, is still feasible to be used to accommodate traffic volume, because the intersection capacity is still greater when compared to traffic volume, because the capacity of each intersection is greater when compared to traffic volume, therefore it can be concluded that for now the JL intersection . Rajawali – JL. Antang, Palangka Raya City, still doesn't need traffic signs in the form of signals. Keywords: unsignalized intersection, performance, intersection capacity, traffic volume.